Advances in Nanostructured Cellulose-based Biomaterials - Carreño, Neftali L V.; Barbosa, Ananda M.; Noremberg, Bruno S.; Salas, Mabel M. S.; Fernandes, Susana C M.; Labidi, Jalel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of the advances on nanostructured celullose from different obtaining forms: natural plants and bacterial microorganisms. It gives the reader an introduction of cellulose focusing in nanosize particles, its potential applications and future perspectives. The potential use of cellulose in the biomedical field is highlighted.
Introduction -- Literature Review: Cellulose Nanostructured -- Material insights -- Cellulose Nanostructured existing forms -- Main applications or uses -- Future perspectives -- Conclusions.
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Biomaterials; Nanochemistry; Regenerative medicine; Nanotechnology; Microsystems and MEMS; Biomaterials; Nanochemistry; Regenerative Medicine and Tissue Engineering